Heterocypris incongruens maintains an egg bank in stormwater habitats and influences the development of larval mosquito, Culex restuans - Jacqueline Trujillo; Cameron D. Schwing; Ephantus J. Muturi; Carla E. Cáceres (Ecology and Evolution, 2023)
Abstract Dormant propagules can provide a rapid colonization source for temporary aquatic habitats and set the trajectory for community dynamics, yet the egg banks of stormwater management systems have received little attention. We asked which species hatched from the sediment of drainage ditches in Champaign County, IL, and found bdelloid rotifers and ostracods (Heterocypris incongruens) to be the most common taxa. These sites also are colonized by mosquitoes, and we established laboratory experiments to examine interspecific interactions between common co‐occurring taxa. Culex restuans larvae were reared in the presence or absence of H. incongruens at two intra‐ and interspecific densities (20 or 40 total individuals) and their survivorship to adulthood, development time to adulthood, adult body size, and sex ratio were determined. Survival for Cx. restuans was significantly lower at high larval density than at low larval density in both treatments. Culex restuans larvae reared in the presence of H. incongruens had a shorter development time to adulthood and emerged as larger adults compared to those reared in the absence of H. incongruens. The sex ratios in the H. incongruens treatments were female‐biased whereas those in the Culex‐only treatments were male‐biased. These differences may have epidemiological implications, as only female mosquitoes serve as disease vectors. Our results emphasize the importance of understanding interspecific interactions in influencing larval mosquito development traits.